Ứng dụng sóng siêu âm để tổng hợp 4-acetyl-3-hydroxy-5-(4- chlorophenyl)-1-phenyl-3-pyrroline-2-one và 4-acetyl-3- hydroxy-5-(4-bromophenyl)-1-phenyl-3-pyrroline-2-one - Nguyễn Trần Ngọc, Trâm (Đà Nẵng, 2026)
Khóa luận Tốt nghiệp - Khoa Lý - Hóa